source : estudyassistant.com

## Which set of steps will translate f(x) = 6x to g(x) = 6x – 5 – 7? a.) shift f(x) = 6x five units to the left and seven units

THIS IS THE COMPLETE QUESTION BELOW;

Which set of steps will translate f(x) = 6x to g(x) = 6x – 5 – 7?

Shift f(x) = 6x five units to the left and seven units up.

Shift f(x) = 6x five units to the right and seven units down.

Shift f(x) = 6x seven units to the right and five units up.

Shift f(x) = 6x seven units to the left and five units down.

Shift f(x)=6x five units to the left and seven units down.

Step-by-step explanation:

We are told to translate the function below

f(x) = 6x to g(x) = 6x – 5 – 7

Which means the process to translate f(x) into g(x) is required.

According to the translation rule

f(x)>f(x)+a

If a<0 it shift to downward

If a>0 it shift to upward

Then we have

(X,y) >((x – 5, y)

There is a shift by x coordinates towards left by 5 units

then we would have the function as

f'(x) = 6(x-5)

Following the translation rule there is a shift by the function by 7 units downward direction then we have

(x,y) >(x,y -7)

Then we have g(x) = 6x – 5 – 7 as our translation product.

Therefore, shift f(x)=6x five units to the left and seven units down.

Find g(f(x)) f(x)=6x-5 , g(x)=(x+5)/6 | Mathway – Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor.Correct answers: 1 question: Which set of steps will translate f(x) = 6x to g(x) = 6x – 5 – 7? a.) shift f(x) = 6x five units to the left and seven units up. b.) shift f(x) = 6x five units to the right and seven units down. c.) shift f(x) = 6x seven units to the right and five units up. d.) shift f(x) = 6x seven units to the left and five units down.In mathematics, a square root of a number x is a number y such that y² = x; in other words, a number y whose square (the result of multiplying the number by itself, or y ⋅ y) is x. For example, 4 and −4 are square roots of 16, because 4² = (−4)² = 16.

Which set of steps will translate f(x) = 6x to g(x) = 6x – Solution for Given f(x) = 6x − 2 and g(x) = 6x − 1, evaluate the composite function. f[g(0)] menu. Products. Subjects. Business. Accounting. Economics. Finance. Leadership. Management. Marketing. Operations Management Experts are waiting 24/7 to provide step-by-step solutions in as fast as 30 minutes!* See Answer1.7 Transformations 123 2 to all of the xvalues of the points on the graph of y= f(x) to e ect a shift to the right 2 units. Generalizing these notions produces the following result.Which set of steps will translate f (x) = 6X to g (x) = 6x – 5 – 7? Shift f (x) = 6* five units to the left and seven units up. O Shift f (x) = 6' five units to the right and seven units down. Shift f (x) = 6X seven units to the right and five units up.

Algebra Calculator | Microsoft Math Solver – Free Pre-Algebra, Algebra, Trigonometry, Calculus, Geometry, Statistics and Chemistry calculators step-by-step This website uses cookies to ensure you get the best experience. By using this website, you agree to our Cookie Policy.Solution for Let f(x)=6x+1 and g(x)=5-x^2 , find (f o g)(x) a. x^2 b.-6x^2+30 c.-6x^2+31 d.-36x^2-12x+4 e. -6x^3-x^2+30x+5Free functions domain calculator – find functions domain step-by-step This website uses cookies to ensure you get the best experience. By using this website, you agree to our Cookie Policy.